تجربة الصناعة المصرفية تايلاند: الإجارة الاقتناء أنموذجًا - Laeba, Muhammad; Hama, Zakariyya (Islamic Yala University, 2010)
This study aims at highlighting the experience of Islamic Banking Industry in Thailand in terms of the history, development, and its role in serving the community as well and the Muslim minority. The study also aims at identifying the Law of the Islamic Bank in Thailand, whether it is relevant to what is being applied in the reality. Finally, some products of leasing and acquisition applied in the Islamic Bank of Thailand were focused to find out whether it conformed with the Islamic jurisprudence and the decision taken by the International Islamic Fiqh Academy as well as the legal standards issued by the Accounting and Auditing Organization for Islamic Financial Institutions. The methodology used in this research is inductive,analytic and applied methods,Moreover, the data of research were collected from various references including personal interview with the Chairman of the Advisory Board of the Islamic Bank of Thailand. The study finds out that there were some prohibitions by the Shariah behind the product of leasing and acquisition. Some of these prohibitions are: the combination between the two contracts i.e. leasing and acquisition, without separating them, the imposition of responsibility for the maintenance of non-operational, warranty of partial loss and insurance on the renter. Another prohibition is the issue of the imposition of compensation for the damage to the tenant in the event of late payment of premiums rental.